Analysis of the Impact of Global Oil Prices On GDP (on the Example of the Azerbaijan Republic) - N. S. Ayyubova (Статистика и экономика)
Purpose of the study. The article analyzes the impact of world oil prices (external and internal factors) on the country’s GDP, considers fluctuations in world oil prices, their impact on the national economy of Azerbaijan and the integrability of these macroeconomic indexes. Materials and methods. The study of the dynamics of the functioning of time series based on the initial data revealed their non-stationarity, which does not allow creating a “qualitative” predictive model. In order to achieve the goals of the study and “improve the quality” of the model being formed, which is used to calculate predictive estimates, appropriate econometric procedures were carried out and the integrability of time series was investigated. In particular, the method of vector error correction model VECM is used. The test is based on the use of cointegration equations between variables, where lag lengths and Granger causality definitions are solved within this model. When forming the VECM model, the hypotheses put forward in the work were tested using econometric tests. The responses of the impulse function to the independent variables of the model were studied by the method of graphical representation based on the values of the model and its residuals.Results. It has been determined that the long-term equilibrium relationship between variables can be considered stable, since after short-term disturbances from shock reactions, stability is restored. The applied method of decomposition of forecast error variances to determine the influence of exogenous variables on the endogenous variable showed that the greatest uncertainty in the forecast for GDP, Azeri_light, Brent and West is given by their own changes during the first trimester of the period under consideration.Conclusion. The results obtained can be useful for identifying real trends in Azerbaijan’s GDP and determining its interdependencies with other macroeconomic variables, for determining its interdependencies with variations in energy prices based on an analysis of the dynamics of the indexes under consideration, for developing recommendations and forming directions for the longterm development of GDP.